ממן18

ממן18 - 18" 1 f 1 n...

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: 18 " 1 ,) f : , .( , , 1 , . n + 3 ~ ( ) , . n .( ~ - (, ) , - ) . f [~ ( )] = n + 3 = f [ ] + 3 : , . m , n , , ( ) ( ) n + m + 5 .1 . f [( ) ( )]= n+ m+ 5= f [ ]+ f [ ]+ 5 f [ ] : N =! ((~ ( A1 )) (( A1 ) (~ ( A2 )))) (( A2 ) (~ ( A3 ))) .2 . f [ ] = 34 , - :' - : - f [ ] N =! f [((~ ( A1 )) N =! f [(~ ( A1 )) (( A1 ) = f [~ ( A1 )] + f [( A1 ) (( A1 ) (~ ( A2 )))) (( A2 ) (~ ( A3 )))] = (~ ( A2 )))] + f [( A2 ) (~ ( A3 ))] + 5 = (~ ( A2 ))] + 5 + f [ A2 ] + f [~ ( A3 )] + 5 + 5 = = f [ A1 ] + 3 + f [ A1 ] + f [~ ( A2 )] + 5 + 5 + 1 + f [ A3 ] + 3 + 5 + 5 = = 1 + 3 + 1 + f [ A2 ] + 3 + 5 + 5 + 1 + 1 + 3 + 5 + 5 = = 1 + 3 + 1 + 1 + 3 + 5 + 5 + 1 + 1 + 3 + 5 + 5 = 34 : - 1 1 - , f [ ] = 1 , .3 .3 . k , m f [ ] = 3k + 1, f [ ] = 3m + 1 - f [~ ( )] , , f [~ ( )] = f [ ] + 3 = (3k + 1) + 3 = 3(k + 1) + 1 , . ~ ( ) : 3 - 1 f [( ) ( )] , . ( ) f [( ) ( )] f [+ f [ + 5 = ] ] = = (3k + 1) + (3m + 1) + 5 = 3(k + m + 2) + 1 ( ) : 3 - 1 2 : . = ( P0 P0 T T T T F F F F P 1 T T F F T T F F P2 T F T F T F T F P0 N T T F F T T T T P 1 P0 T F T F T T T T P2 ~ ( P0 F T F T F F F F P) 1 ~ ( P0 P2 ) P2 ) P2 ) *= ( P0 P ) ~ ( P0 1 F T T T F F F F , = T , P0 , P , P2 1 : . (~ ( (~ 1 ( (~ 1 (~ . ( P0 P P2 )) P0 P ) P2 ) P0 P ) P2 )) 1 , , = F , P0 , P , P2 1 . , : . ((~ P0 ) P ) P2 )) P0 P ) P2 )) P0 P ) P2 ) (~ 1 (~ ( (~ 1 (~ ( (~ 1 P0 P P2 )) P0 P P2 ) ( (~ ( 1 1 .1 .2 3 : . : A1 . : A2 . : A3 .1 . : A4 :( ) a =~ ( A1 b ( A3 A2 ) A4= ) A1 c = A3 (~ A2 ) A3 d = (~ A2 ) e = A1 (~ A2 ) .2 . a, e : A1 , A2 A1 T T F F A2 T F T F A1 A2 T F F F a =~ ( A1 A2 ) ~ A2 F F T T T F T T e = A1 (~ A2 ) F T T F (1) , e - a - . . a, b, c , {a, b} |= c (2) A1 T T T T T T T T F F F F F F F F A2 T T T T F F F F T T T T F F F F A3 T T F F T T F F T T F F T T F F A4 T F T F T F T F T F T F T F T F a F F F F T T T T T T T T T T T T A3 4 =b ( A3 A == T T T F T T T F T T T F T T T F A4 ) T T T T T T T F F F F T F F F T A1 ~ A2 F F F F T T T T F F F F T T T T c A3 F F T T T T T T F F T T T T T T (~ A2 ) J (a ) = T J , . {a, b} |= c . J (c ) = T , J (b) = T : (3) A1 T T T T T T T T F F F F F F F F A2 T T T T F F F F T T T T F F F F A3 T T F F T T F F T T F F T T F F A4 T F T F T F T F T F T F T F T F a F F F F T T T T T T T T T T T T c F F T T T T T T F F T T T T T T ~ A2 F F F F T T T T F F F F T T T T d = (~ A2 ) T T T T T T F F T T T T T T F F A3 b T T T T T T T F F F F T F F F T , b {a, c, d } ,11 . J (b) = F , J (a ) = T , J (c) = T , J (d ) = T 4 . = , . .1 . , |= = , , J ( ) = T , J ( ) = F J , |= ) |= , J ( ) = J ( ) = F , .( F T J . . J ( ) = T J ( ) = T , J ( ) = T . J ( ) = F J ( ) = T , . T |= |= - , J ( ) = T J ( ) = T , . - J ( ) = T . |= .2 . J ( ) = T , . J ( ) = T J . |= , J (~ ) = T , J ( ) = T - , |= ~ .3 , . J ( ) = F . , ...
View Full Document

This note was uploaded on 07/23/2009 for the course MATH. 04101 taught by Professor ישראלפרידמן during the Summer '06 term at The Open University.

Ask a homework question - tutors are online